PENDAMPINGAN DAN PELATIHAN PENYUSUNAN MODUL AJAR UNTUK OPTIMALISASI IMPLEMENTASI KURIKULUM MERDEKA DI SD 2 MALOMBA - Ni Kadek Sri Andini; Dela Maulana; Sitti Nuralan (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The implementation of the Independent Curriculum requires teachers to have the ability to develop learning modules that are tailored to student needs and school conditions. However, many elementary school teachers still experience difficulties in designing learning modules that are systematic, contextual, and oriented towards learning outcomes. Therefore, this community service activity was carried out at Malomba 2 Elementary School with the aim of improving teacher competency in developing learning modules. The implementation methods included lectures, training, mentoring, and hands-on practice in developing learning modules. The results of the activity showed an increase in teachers' understanding of the structure of learning modules and their ability to produce learning modules that meet the Independent Curriculum standards. Furthermore, there was an increase in teacher interest and motivation to develop creative and relevant learning within the school context. Based on these findings, it is recommended that further training be conducted regularly and continuously to strengthen the implementation of the Independent Curriculum in elementary schools.